2021
DOI: 10.3390/molecules26102994
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Selected Criteria Enabling Optimization of the Extraction of Polar Biologically Active Compounds from Alfalfa with Supercritical Carbon Dioxide

Abstract: The aim of this research was to provide crucial and useful data about the selection of the optimization criteria of supercritical carbon dioxide extraction of alfalfa at a quarter-technical plant. The correlation between more general output, including total phenolics and flavonoids content, and a more specified composition of polar constituents was extensively studied. In all alfalfa extracts, polar bioactive constituents were analyzed by both spectrometric (general output) and chromatographic (detailed output… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The highest MYR, as the most abundant flavonoid in bound extract, had foreign cultivar Florida 66 (502.2 μg/g dm), which is 4.3 times more than the lowest value in OS 101 (117.1 μg/g dm) ( Figure 3 b; Table S4 ). In alfalfa samples, in addition to the flavonoids found in our research, some authors also mentioned glabridin, naringin, and luteolin as major flavonoids [ 13 , 36 , 40 , 41 , 42 ].…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The highest MYR, as the most abundant flavonoid in bound extract, had foreign cultivar Florida 66 (502.2 μg/g dm), which is 4.3 times more than the lowest value in OS 101 (117.1 μg/g dm) ( Figure 3 b; Table S4 ). In alfalfa samples, in addition to the flavonoids found in our research, some authors also mentioned glabridin, naringin, and luteolin as major flavonoids [ 13 , 36 , 40 , 41 , 42 ].…”
Section: Resultssupporting
confidence: 65%
“…), used analytical technique (HPLC, HPLC-MS, HPLC-MS/MS, etc. ), and alfalfa part (aerial or roots) [ 16 , 35 , 36 ]. Newby et al [ 37 ] determined the dominance of alkali-labile bound phenolic acids in relation to soluble ones (less than 2%).…”
Section: Resultsmentioning
confidence: 99%
“…The high-pressure treatment in the SFE process could better destroy the camellia seed cells, rendering the extractant to enter the cells to extract the oil. Moreover, the high oil yield of SFE was also connected with the excellent extraction performance of CO2 (Wrona et al, 2021). Figure 3B shows the microstructure of camellia seed cake after AE.…”
Section: Microstructure Analysis Of Camellia Seed Cakes With Differen...mentioning
confidence: 86%
“…However, it is difficult to implement this technology at a large commercial scale due to the large amounts of co-solvents required. Consequently, it was recently proposed that CO 2 should be used as the only solvent to extract polyphenols from produce using SFAE [ 53 ]. These authors optimized the temperature, pressure, and solvent flow required to isolate phytochemicals from alfalfa and showed that SFAE could be used to efficiently isolate both phenolic acids and flavonoids.…”
Section: Isolation Of Bioactive Agents From Botanical Sourcesmentioning
confidence: 99%